2011
DOI: 10.1159/000325829
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Multiple System Atrophy and Progressive Supranuclear Palsy

Abstract: Objective: Multiple system atrophy (MSA) and progressive supranuclear palsy (PSP), known as atypical parkinsonian syndromes (APS), are neurodegenerative disorders with severe disability and decreased life expectancy. Little is known about the health-related quality of life (HrQoL) and its determinants in patients with those disorders. The objective of our cross-sectional study was to evaluate the HrQoL in patients with APS and to identify the determinants of HrQoL. Methods: A total of 101 consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
43
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 70 publications
(63 reference statements)
13
43
3
1
Order By: Relevance
“…A quality-of-life study published after the completion of our focus groups suggests that educating patients about PSP could improve health-related quality of life because a low level of education was an independent determinant of decreased quality of life. 13 Our findings support the call for patient education, but also point to the need to expand efforts to include education of health care providers.…”
Section: Discussionsupporting
confidence: 70%
“…A quality-of-life study published after the completion of our focus groups suggests that educating patients about PSP could improve health-related quality of life because a low level of education was an independent determinant of decreased quality of life. 13 Our findings support the call for patient education, but also point to the need to expand efforts to include education of health care providers.…”
Section: Discussionsupporting
confidence: 70%
“…The comparison of the SF-36 and EQ-5D between the two subtypes, after adjusting for disease duration, showed that MSA-P patients had worse PCS and MCS, as indicated by their scores on the SF-36, and worse pain/discomfort and anxiety/depression, according to their scores on the EQ-5D. The presence of parkinsonism seemed to bring about a more serious decline in HrQoL than the presence of cerebellar dysfunction, which is inconsistent with the results of another study (Winter et al, 2011). HrQoL was negatively associated with increased motor impairment and disease severity, as assessed by the HY staging scale and the UMSARS, indicating that disease progression contributed to the deterioration of HrQoL, previous studies have also confirmed these results (Chen et al, 2014;Schrag et al, 2006Schrag et al, , 2010Winter et al, 2011).…”
Section: Discussioncontrasting
confidence: 66%
“…HrQoL was negatively associated with increased motor impairment and disease severity, as assessed by the HY staging scale and the UMSARS, indicating that disease progression contributed to the deterioration of HrQoL, previous studies have also confirmed these results (Chen et al, ; Schrag et al, ; Winter et al, ). Depression and anxiety scores were moderately correlated with HrQoL scores; other studies have reported a close association between depression and HrQoL (Schrag et al, ; Winter et al, ; Zhang et al, ). Autonomic dysfunction was correlated with HrQoL in one study (Schrag et al, ), but only a weak correlation with the HrQoL was found in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…1 As in other neurodegenerative conditions, patients with PSP also display difficulties with cognition, 2 psychiatric functioning, 3 and quality of life. 4 Functional disability observed in these patients is less clear, however.…”
mentioning
confidence: 96%